2022
DOI: 10.3390/jmse10101424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Temperature on the Undrained Shear Strength of Deep-Sea Clay by Mini-Ball Penetration Tests

Abstract: The technology for in situ testing of the undrained shear strength of deep-sea clay is underdeveloped. Indoor tests remain necessary, and there is a large temperature difference between in situ and laboratory tests. To analyse the effect of temperature on undrained shear strength, in this study the physical characteristics of marine clay samples from the South China Sea were determined, followed by penetration tests by the mini-ball method under low (4 °C) and room (20 °C) temperatures. The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Gu et al [10] investigated the low-temperature effect on the undrained shear strength of undisturbed marine clay samples from the South China Sea using a full-flow penetrometer. They found that the undrained shear strength at an in situ temperature (4 • C) is bigger than at room temperature (20 • C), which is valuable for offshore geotechnical engineers.…”
Section: Papers Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gu et al [10] investigated the low-temperature effect on the undrained shear strength of undisturbed marine clay samples from the South China Sea using a full-flow penetrometer. They found that the undrained shear strength at an in situ temperature (4 • C) is bigger than at room temperature (20 • C), which is valuable for offshore geotechnical engineers.…”
Section: Papers Detailsmentioning
confidence: 99%
“…The SI includes 1 review paper [1] and 13 research papers [2][3][4][5][6][7][8][9][10][11][12][13][14] that cover different aspects related to the subject. A total of 95 scholars from universities, research institutions, and industries have contributed to this SI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation